Characterization of Bacillus species from Fresh Fruits and Their Biodegradation Potential in the Reduction of Heavy Metal Contents in Banana Juices - Olateru, Comfort Tosin; Ajulor, Praise Nosakhare; Nwaokolo, Victoria Modupe; Ugwu, Juliana Amaka (Journal of Science, Technology and Innovation Research, 2025)
Fresh fruits are important sources of bioactive compounds, but are vulnerable to spoilage after harvesting; spoilt fruits have been shown to be reservoirs of both microorganisms and heavy metals. The biological method of decontamination of heavy metals has been reported to be safer for the environment and living organisms. In this study, fresh fruits comprising of oranges, lime, apples, and pineapples were bought from a fruit market in the Ibadan metropolis for the enumeration of Bacillus species using nutrients and De Man Rogosa Sharpe media. Identification of presumptive Bacillus species was done using phenotypic and molecular tests. Amylolytic screening was done using the starch agar plate method. Biodegradation of lead, iron, zinc, cobalt and copper were monitored inside pasteurized banana juice inoculated with Bacillus haynesii and Bacillus subtilis and uninoculated banana juice for a period of five days using analytical methods. Statistical analysis by means of one-way analysis of variance. A total of thirty-five Bacillus species were obtained in this study, of which Bacillus cereus, Bacillus subtilis and Bacillus haynesii were amylolytic; accession numbers of selected isolates are Bacillus subtilis and Bacillus spp. are MG850841 and MG850846, only lead and copper were significantly reduced in both control and inoculated juices while there was no significant difference in decreasing iron, zinc, and cobalt content in both inoculated and uninoculated banana juices. This study observed that Bacillus species are abundant in fresh fruits and they can be harnessed for decontamination of certain objectionable metals in the environment. Keywords: Bacillus species, Biodegradation, Heavy metals, Juices